2020
DOI: 10.1186/s13075-020-2146-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived exosomal microRNA-124-3p attenuates neurological damage in spinal cord ischemia-reperfusion injury by downregulating Ern1 and promoting M2 macrophage polarization

Abstract: Background: Spinal cord ischemia-reperfusion injury (SCIRI) often leads to neurological damage and mortality. In this regard, understanding the pathology of SCIRI and preventing its development are of great clinic value. Methods: Herein, we analyzed the role of bone marrow mesenchymal stem cell (BMMSC)-derived exosomal microRNA (miR)-124-3p in SCIRI. A SCIRI rat model was established, and the expression of Ern1 and M2 macrophage polarization markers (Arg1, Ym1, and Fizz) was determined using immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 23 publications
0
81
1
Order By: Relevance
“…As a result, they play an essential role in intercellular communication through the transfer of genetic material [ 26 , 27 ]. Recent studies have focused on exosomal contents, including proteins and RNAs, and attempted to determine their underlying mechanisms in the treatment of various diseases [ 25 , 28 31 ]. It has been shown that exosomal miRNAs can exert their regulatory effects on target cells, thus representing a new mode of intracellular communication [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they play an essential role in intercellular communication through the transfer of genetic material [ 26 , 27 ]. Recent studies have focused on exosomal contents, including proteins and RNAs, and attempted to determine their underlying mechanisms in the treatment of various diseases [ 25 , 28 31 ]. It has been shown that exosomal miRNAs can exert their regulatory effects on target cells, thus representing a new mode of intracellular communication [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-126 is validated to suppress oxidative stress by increasing superoxide dismutase (SOD) and decreasing malondialdehyde (MDA) in I/R-induced renal models of mice [ 26 ]. As a widely explored miRNA, miR-124-3p has been documented to exert critical roles in I/R-caused injury [ 27 , 28 ]. Liang et al have indicated that upregulation of miR-124-3p reduces H/R-caused production of tumor necrosis factor-alpha (TNF- α ), interleukin-1 beta (IL-1 β ), and IL-6 in human cardiac myocytes [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al have indicated that upregulation of miR-124-3p reduces H/R-caused production of tumor necrosis factor-alpha (TNF- α ), interleukin-1 beta (IL-1 β ), and IL-6 in human cardiac myocytes [ 27 ]. Li et al have declared that increasing miR-124-3p attenuates I/R-induced nerve injury in the spinal cord [ 28 ]. Nonetheless, the modulation of miR-124-3p by SNHG14 in I/R-induced renal injury has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…MSC-exosomes can regulate macrophage/microglial polarization through regulation of pathways by exogenous miRNAs and long ncRNAs (lncRNAs). Endoplasmic reticulum stress is induced after SCI [102], and miR-124-3p can inhibit the expression of the endoplasmic reticulum to nucleus signaling 1, which is a major regulator of endoplasmic reticulum stress [87]. Exogenous miR-124-3p is transferred to macrophages through MSC-exosomes and enhances the polarization of M2 macrophages by inhibiting the expression of endoplasmic reticulum to nucleus signaling 1 [87].…”
Section: Ren Et Almentioning
confidence: 99%
“…Endoplasmic reticulum stress is induced after SCI [102], and miR-124-3p can inhibit the expression of the endoplasmic reticulum to nucleus signaling 1, which is a major regulator of endoplasmic reticulum stress [87]. Exogenous miR-124-3p is transferred to macrophages through MSC-exosomes and enhances the polarization of M2 macrophages by inhibiting the expression of endoplasmic reticulum to nucleus signaling 1 [87]. In addition, MSC-exosomes carrying miR-216a-5p activate phosphatidylinositide 3-kinases (PI3K)/serine/threonine kinase (AKT), inhibit the Toll-like receptor 4/nuclear factor kappa B (NF-kB) signaling pathways, and transform M1 microglia into M2 microglia [83].…”
Section: Ren Et Almentioning
confidence: 99%